2008
DOI: 10.1080/15313220802410054
|View full text |Cite
|
Sign up to set email alerts
|

How to Increase Response Rates When Surveying Hospitality Managers for Curriculum-Related Research: Lessons from Past Studies and Interviews with Lodging Professionals

Abstract: Continuous industry input is needed to keep hospitality management curricula current, relevant, and applicable. However, barriers including low response rates are reported when surveying hospitality professionals about competencies and skills essential for success. In response, this study sought to identify successful strategies used by researchers when surveying hospitality managers through mail surveys. Interviews conducted with lodging managers indicated potential strategies for increasing response rates wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Of the 836 questionnaires sent to hotel and restaurant managers in a Midwestern state of the United States, 124 were returned for a response rate of 15%. A similar response rate (14%) was achieved by in their study of foodservice operations; Ravichandran and Arendt (2008) reported response rates in hospitality lodging research ranged from 11% to 93%. Of the 124 returned and analyzed questionnaires, 63 (51%) were from restaurant managers and 61 (49%) from hotel managers.…”
Section: Respondents' Profilesupporting
confidence: 68%
“…Of the 836 questionnaires sent to hotel and restaurant managers in a Midwestern state of the United States, 124 were returned for a response rate of 15%. A similar response rate (14%) was achieved by in their study of foodservice operations; Ravichandran and Arendt (2008) reported response rates in hospitality lodging research ranged from 11% to 93%. Of the 124 returned and analyzed questionnaires, 63 (51%) were from restaurant managers and 61 (49%) from hotel managers.…”
Section: Respondents' Profilesupporting
confidence: 68%
“…The personal touch added to the distribution and collection methods resulted in a high response rate. The researchers followed recommendations by Ravichandran and Arendt (2008). Contacting key figures, such as the general manager, prior to visiting or sending questionnaires is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Omani scholars have suggested that researchers should gather information from Omani organizations by taking advantage of their personal and informal contacts [81; 82; 83]. It has also been suggested that making initial contact with a key corporate representative may increase response rate [84].…”
Section: The Study Procedures For the Collection Of Quantitative Datamentioning
confidence: 99%